Análise e comparação do comportamento da ionosfera e do posicionamento por ponto em períodos de alta e baixa atividade solar - Salomoni, Christiane Silva; Matsuoka, Marcelo Tomio; de Souza, Sérgio Florêncio; Camargo, Paulo de Oliveira [UNESP] (My University, 2009)
The ionosphere is a major source of systematic error in the GPS observables. As this error is directly proportional to the TEC (Total Electron Content), the quality of GPS positioning (especially with single frequency receivers) can be significantly affected by regular changes of TEC. The ionosphere factor is even more relevant in the Brazilian region, where ionospheric phenomena, such as the Equatorial Anomaly, intensify these variations. Taking the above mentioned factors into account, experiments were conducted in this research to evaluate the daily and seasonal behavior of the TEC and the point positioning with GPS (single frequency) in periods of high and low solar activity in the Brazilian region. The results showed a direct correlation between the decrease in electrons density in the ionosphere (period of low solar activity) and improvement in positioning accuracy, as well as a large influence of Equatorial Anomaly on the results of point positioning.
Analysis and comparison of ionosphere behavior and point positioning in periods of high and low solar activity
Keywords: GPS Positioning; Ionosphere; TEC